QSAR modeling of cumulative environmental end-points for the prioritization of hazardous chemicals. Issue 1 (11th December 2017) - Gramatica, Paola; Papa, Ester; Sangion, Alessandro
Abstract : Indexes for the prioritization of potential hazardous chemicals can be derived and modelled by combining PCA and QSAR models. Abstract : The hazard of chemicals in the environment is inherently related to the molecular structure and derives simultaneously from various chemical properties/activities/reactivities. Models based on Quantitative Structure Activity Relationships (QSARs) are useful to screen, rank and prioritize chemicals that may have an adverse impact on humans and the environment. This paper reviews a selection of QSAR models (based on theoretical molecular descriptors) developed for cumulative multivariate endpoints, which were derived by mathematical combination of multiple effects and properties. The cumulative end-points provide an integrated holistic point of view to address environmentally relevant properties of chemicals.